B0‐orientation dependent magnetic susceptibility‐induced white matter contrast in the human brainstem at 11.7T. Issue 6 (28th March 2016) - Aggarwal, Manisha; Kageyama, Yusuke; Li, Xu; van Zijl, Peter C.
Abstract : Purpose: To investigate B0 ‐field‐orientation dependent white matter contrast in the human brainstem based on R2 * and frequency difference (Δ f ) mapping from gradient echo (GRE) imaging at 11.7T. Methods: Multi‐echo GRE data were acquired from two fixed human brainstem specimens at multiple orientations with respect to the static B0 field. The B0 ‐orientation dependent modulation curves of R2 * and Δ f measurements between short and long echo time regimes were used to reconstruct maps of three‐dimensional (3D) white matter orientation vectors. The results were compared with maps from diffusion MRI, susceptibility tensor imaging, and histological staining of the same specimens. Results: R2 * and Δ f maps demonstrated distinct and significant contrast modulation between the corticospinal tract (CST) and transverse pontine fibers (TPF) dependent on B0 orientation. Interleaved fiber orientations of the CST and TPF could be sensitively resolved based on field‐orientation‐dependent fitting of the R2 * and Δ f measurements. The fitted 3D orientation vector maps and peak‐to‐peak amplitude of R2 * and Δ f modulation exhibited close correspondence to primary eigenvector and anisotropy maps derived from diffusion MRI. The amplitude of B0 ‐orientation dependent R2 * modulation was significantly ( P < 0.005) higher in the CST compared with TPF, while fractional anisotropies were comparable. Conclusion: The findings of this study demonstrate the potential of B0 ‐orientation dependent susceptibility‐induced R2 * and Δ f contrasts to probe tract‐specific orientation and microstructure in white matter. Magn Reson Med 75:2455–2463, 2016. © 2016 Wiley Periodicals, Inc.